Determinants of Capital Expenditure in the Government of North Sumatra for the Years 2020-2022 - Purba, Benhard Sebastian; Manullang, Stefanus Efrata; Zain, Jenny; Syahputra, Oky (Lembaga Riset Ilmiah, 2024)
This study describes factor affecting budget capital expenditure, among them is expenditure government. Big small expenditure government very depends on income that accepted by the government itself. One of the factors that influence Budget Capital Expenditure in a government that is Income Local Original Revenue (PAD), General Allocation Fund (DAU), Allocation Fund Special (DAK), and Revenue Sharing Fund (DBH). Increasingly big income received by the government area will the moregood because influence in a way positive budget shopping in the area the. The purpose of This research is to analyze Local Original Income (PAD), Funds Allocation General (DAU), Funds Allocation Special (DAK), and Funds for Results (DBH), influential or not to Budget Capital Expenditure in North Sumatra Province. Engineering analysis used is technique multiple linear analysis, results study that in a way partial only Local Original Income (PAD), General Allocation Fund (DAU), and Regional Allocation Fund (RAF) Special (DAK) marked positive or influential significant to Budget Capital Expenditure in Sumatra Province North, while the Revenue Sharing Fund (DBH) is marked negative or has no effect significant to Budget Shopping in Sumatra Province North.